Customer Relationship Management In Banking Sector Case Study Of Conventional Banks - Dennis Rydarto Tambunan; Heru Kreshna Reza; Melly Susanti; Sabri (Publisher Cv. Inara, 2021)
The importance of Customer Relationship Management (CRM) to help businesses acquire new customers, retain existing ones and maximize their lifetime value. This paper discusses the role of Customer Relationship Management in 4 bank units and the need for Customer Relationship Management to increase customer value by using several analytical methods in CRM applications. This paper attempts to identify the technological revolution witnessed by commercial banks and to what extent it has benefited banks to build better customer relationship management (CRM) services between public sector banks and private sector banks. The purpose of this study is 1) to analyze customer opinions about bank CRM in relation to service quality management. 2) To find out the customer's opinion about the bank's CRM on customer relationship management. This study uses primary and secondary data. Primary data will be collected by distributing structured questionnaires to conventional banks (Private and Government). Secondary data will be collected from records published by the financial services authority (OJS), standard textbooks and published research papers, and through web information. The primary data required will be collected from 6 banks in Bengkulu. In addition to collecting information from banks, it also collects information from the general public who have bank accounts.